Pengertian dan Sumber Ajaran Islam Berdasarkan Kajian Metodologi Studi Islam - Rychan Islah Ramadhan; Ziana Farihatul Walida; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to comprehensively understand the definition of the sources of Islamic teachings, explain the meaning of the Qur'an along with its contents and basic legal components, understand the meaning of Hadith/Sunnah along with its functions and types as the second source of Islamic law, as well as understand the meaning of ijtihad, its types, and its function in answering the problems of the ummah. The method used is library research with a descriptive-analytical approach to literature related to ushul fiqh and sources of Islamic law. The results show that the sources of Islamic teachings are divided into primary sources (Qur'an and Hadith) and secondary sources (ijtihad). The Qur'an contains teachings on monotheism (tauhid), worship, promise and threat, stories of past nations, news of the afterlife, as well as principles of knowledge. Hadith functions as a strengthener, explainer, specifier, and establisher of laws not found in the Qur'an. Ijtihad includes ijma', qiyas, istihsan, mashalih murshalah, saddu dzariah, istishab, and 'urf. A correct understanding of the sources of Islamic teachings is very important so that Islamic teachings can be practiced properly in daily life.